The clash between physical and digital realm: hybrid movement training during the pandemic - Bilge Serdar (Springer, 2024)
Abstract This article is based on ethnographic research conducted in one of the physical training institutions that offer the Laban/Bartenieff Movement Studies (LBMS) certification program in 2021. Because of the COVID-19 pandemic crisis, the training was held in a hybrid format in which some participants were in the studio while others were attending remotely via Zoom. Zoom-mediated movement training for long hours revealed how the intervention of telematic technologies challenged practitioners' sensorial experience and sense-making process. Moreover, bringing co-located and remote participants' experiences together in the hybrid setting disclosed different modes of interaction dynamics in the studio and online. Overall, participants described their hybrid experience as a clash. In the article, starting from unfolding those clashes from the enactive perspective, I discuss how remote intercorporeality through an audio-video streaming system, Zoom, challenges participants' sensorial experience and how remote interaction affects the shared sense-making process in the hybrid format setting.